Intake of Seven Essential Amino Acids Improves Cognitive Function and Psychological and Social Function in Middle-Aged and Older Adults: A Double-Blind, Randomized, Placebo-Controlled Trial - Suzuki, Hiroyuki; Yamashiro, Daichi; Ogawa, Susumu; Kobayashi, Momoko; Cho, Daisuke; Iizuka, Ai; Tsukamoto-Yasui, Masako; Takada, Michihiro; Isokawa, Muneki; Nagao, Kenji; Fujiwara, Yoshinori (Frontiers in Nutrition, 2020)
Protein malnutrition is a potential risk factor for senile dementia, although the precise link between protein/amino acid nutrition and cognitive function is unknown. The purpose of this study was to examine the effect of the ingestion of seven selected essential amino acids as a granular powder rich in leucine, phenylalanine, and lysine on cognitive and psychosocial functions in healthy adults. A double-blind, randomized, placebo-controlled trial was conducted. A total of 105 participants aged 55 years or older were randomly assigned to one of three groups: daily ingestion of 3 g (3gIG) or 6 g (6gIG) of the selected amino acids or daily ingestion of a placebo (PCG). Each group ingested the test powder for 12 weeks. As the main outcome, cognitive function was assessed before and after ingestion by a cognitive test battery. Psychosocial functions were also examined. Analysis of covariance revealed that the 6gIG showed significantly improved cognitive function (Trail Making Test B), social interaction and psychological health scores after ingestion compared to the PCG (multiplicity adjusted p < .05). These findings suggested that ingestion of the seven essential amino acids led to improved working memory and psychosocial functioning, which is expected to prevent cognitive decline.